2003
DOI: 10.1037/0097-7403.29.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Importance of trials versus accumulating time across trials in partially reinforced appetitive conditioning.

Abstract: Four experiments with rats examined partial reinforcement in appetitive conditioning. In Experiment 1, adding nonreinforced trials to a continuous reinforcement schedule slowed acquisition, whereas deleting reinforcers did not. Trial massing suppressed performance and learning. In Experiment 2, conditioning with a short conditioned stimulus (CS) was rapid, and partial reinforcement with a short CS was as effective as continuous reinforcement with equal accumulated time in the CS. In Experiment 3, conditioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
123
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(140 citation statements)
references
References 25 publications
13
123
4
Order By: Relevance
“…Thus our experiments did not confirm the difference in responding that was evident, although not statistically significant, in Experiment 2 of Bouton and Sunsay (2003). This is despite the fact that our within-subjects design should be more sensitive to differences between conditions than their betweensubjects design.…”
Section: Methodscontrasting
confidence: 69%
See 4 more Smart Citations
“…Thus our experiments did not confirm the difference in responding that was evident, although not statistically significant, in Experiment 2 of Bouton and Sunsay (2003). This is despite the fact that our within-subjects design should be more sensitive to differences between conditions than their betweensubjects design.…”
Section: Methodscontrasting
confidence: 69%
“…However, the comparison of particular interest is between rats' responses to the long 100% CS and the short 33% CS, since these have the same cumulative rate of reinforcement (one US per 60 s of CS). If, as predicted by some real-time trial-based models of conditioning and suggested by the results reported in Bouton and Sunsay (2003), conditioning is affected by trial structure, then D there should be a difference in the rats' response rates to the two CSs. However, if trial structure is irrelevant and rats simply accumulate learning about non-reinforcement across CS exposure, then they should show similar levels and rates of conditioning to the two CSs…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations